Diagnosis and Assessment of Dental Caries by Clinical Steps and Caries Detection Dye Solution: Diagnosis dan Penilaian Karies Gigi dengan Langkah Klinis dan Larutan Pewarna Pendeteksi Karies - Salih, Nabra F. (Indonesian Journal on Health Science and Medicine, 2024)
This research compares the effectiveness of caries reagent dye (CDD) with traditional diagnostic techniques for identifying carious dentin in deep cavities. The research, which was carried out at the clinics of Thi-Qar University/College of Dentistry, included the voluntary enrollment of 70 people with deep-rooted caries, ages 18 to 40. Every patient got standard dental care, and all patients were made aware of the goal and methodology of our study. Seventy teeth from seventy individuals with proximal or occlusal caries (one tooth from each patient) made up the final sample. Age: 18–40 years old, free of systemic illnesses. No clinical indications or symptoms of pulpal damage, and active and severe dentin caries affecting the occlusal and/or proximal surfaces of permanent molars and premolars, i.e., deep- caries with direct access and vision. Patients with pulp-related dental caries, intra- or extraoral swellings, systemic diseases, or any periapical conditions. Additionally, any main caries were not included. One tooth was chosen at random for each participant, yielding 70 teeth from patients with proximal (P) and/or occlusal (O) caries lesions. Caries reagent dye (CDD) was used to assess the same 70 teeth that had been clinically examined for the presence of caries using straightforward conventional diagnostic techniques. The operator began the drilling process after using preoperative pulp vitality checks to make sure there was no pulpal damage. Beginning with a slow-speed handpiece, a level surface was created and the dentine lesion was visible for both the occlusal (A) and proximal (B) cavities. Then, using a traditional round steel drill in a reverse-angled handpiece to lower the speed (400 rpm), the carious dentine was manually removed. A dental explorer was used to measure the dentine's hardness. This was done repeatedly until all of the teeth were checked with a dental explorer and either had a leather-like texture or made a harsh scratching sound. Several students, acting as inexperienced examiners, carried out the caries removal process in every topic. Following visual inspections, CDD was used to determine if residual caries was present or not. Uninfected dentin will not absorb much of the stain, however demineralized dentin will exhibit distinct staining patches. We determine if there is a positive or negative caries outcome after assessing the cavity using the two measures. As a result, The stain test results showed that 70 individuals were examined both before and after applying the stain, according to the statistics of paired samples. The results showed that the stain had a significant impact on the test on teeth as inexperienced evaluators, with the arithmetic mean after the stain being 0.71 and the arithmetic mean before the stain being 0.56 with a difference of 0.15. The (t) test value was 2.488. Conclusion, This study shows the importance of using the CDD for the beginner students and that it has a greater effective impact for its use in diagnosis and its impact in identifying deep caries is greater than the usual clinical diagnosis among students, and this is only at the student level, so the percentages could be different if the evaluators have more experience Highlights: Compare CDD effectiveness vs. traditional methods for diagnosing deep caries. 70 teeth analyzed; CDD enhanced inexperienced students' diagnostic accuracy. CDD significantly improves caries detection, especially for beginner dental students. Keywords: Caries Reagent Dye, Deep Caries, Dental Diagnosis, Beginner Students, Clinical Effectiveness